(untitled) (Cardiovascular Journal, 2012)
Background: Aim of the study was to assess the safety of the trans-radial Percutaneous coronary intervention (PCI) than conventional Trans-femoral approach by using either Bare-metal stents (BMS) and or Drug Eluting Stent (DES) like Sirolimus-eluting or Paclitaxel-eluting stent. Also to see its safety in regards of procedural time, quick mobilization, less complication and less radiation exposure. Methods: Total 117 patients were randomized from a total of 538 patients who had PCI at our center in the quantifying period. Total 130 stent deployed in 117 patients. Among the patients, Male: 100 and Female:17. Mean age were for Male: 55yrs, for Female: 57yrs. Associated Coronary artery disease (CAD) risk factors were Dyslipidemia, High Blood pressure, Diabetes Mellitus, Positive FH for CAD and Smoking (all male). Results: Our study shows 21.7% had trans-radial PCI. Among the study group; 72 (61.5%) were Dyslipidemic, 75 (64.1%) were hypertensive: 47(40.2%) patients were Diabetic, FH 29 (24.8%) and 33(33%) were all male smoker. Female patients were more obese (BMI M 27: F 29) and developed CAD in advance age. Common stented territory were LAD 51 (43.6%) followed by RCA 41 (35%) and LCX 27(23%). Average length and diameter of stented vessel were almost same in all territory. Territory wise multiple or overlapping stenting was done in LAD 3 (6 stents), RCA 1(2stents), LCX 4 (10 stents). Stent used: BMS 37 (28.5%), Sirolimus 41(31.5%), Paclitaxel 27 (21%), Everolimus 22 (16.9%), Biolimus 2 (1.5%) and Zotarolimus 1(0.75%). Less Procedural time, reduced radiation exposure, no procedural complication and overall better patient comfort were observed. Conclusion: Our study has revealed that trans-radial PCI is safe with reduced radiation exposure, quick mobilization of patient and no procedural complication in all the case, indicates it can be done routinely as an alternative to conventional Trans-femoral approach. DOI: http://dx.doi.org/10.3329/cardio.v5i1.12274 Cardiovasc. j. 2012; 5(1): 57-61